Socialization of Maladministration-Free Public Services within the Jurisdiction of the Ombudsman Representative Office of the Republic of Indonesia, Central Java Province - Kun Retno Handayani; Martitah Martitah; Indah Sri Utari; Yuli Prasetyo Adhi; Rahmawati Mohd. Yusoff (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
The public continuously demands high-quality public services from the government. However, these expectations are often unmet because public service delivery remains characterized by bureaucratic complexity, inefficiency, legal uncertainty, and procedures that are perceived as burdensome. To ensure that public services are delivered effectively and in accordance with the principles of good governance, robust external oversight is essential. In this regard, the Indonesian Ombudsman plays a central role as an independent supervisory institution responsible for preventing maladministration and safeguarding citizens’ rights in public service delivery. This community service initiative, implemented in collaboration with the Representative Office of the Indonesian Ombudsman for Central Java Province, employed several approaches, including audiovisual public education through an interactive dialogue program on RRI Pro 1 Semarang, the establishment of community networks concerned with maladministration, the Ombudsman on The Spot outreach program, and quantitative evaluation using the Public Service Delivery Compliance Survey, which has been transformed into the Ombudsman Opinion starting in 2025. These initiatives contribute to strengthening public awareness, increasing community participation, and improving institutional accountability in public services. The Representative Office of the Indonesian Ombudsman for Central Java Province has successfully resolved hundreds of public complaints with a resolution rate of approximately 90 percent through participatory approaches, mediation, conciliation, and formal recommendations. Furthermore, the expansion of service accessibility through Ombudsman on The Spot and digital reporting applications has enabled residents, particularly those in rural areas of Central Java, to report maladministration more quickly and effectively. These initiatives contribute to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 16 (Peace, Justice and Strong Institutions), by promoting transparent, accountable, inclusive, and citizen-centered public institutions while strengthening public participation in governance and enhancing access to justice through effective oversight mechanisms.